1986
DOI: 10.1111/j.1748-1716.1986.tb07952.x
|View full text |Cite
|
Sign up to set email alerts
|

Some cardiovascular and metabolic effects of repeated sauna bathing

Abstract: Ten healthy male volunteers were exposed to the dry heat of a Finnish sauna (+80 degrees C) for 1 h twice a day for a period of 7 days. After each exposure rectal temperature rose by 0.8-1.1 degrees C and body weight dropped by 0.7-0.9 kg. The systolic blood pressure recorded 3-5 min after the sauna did not change during the experiments but the diastolic blood pressure decreased by 7-37 mmHg (P less than 0.05). The pulse rate rose from 75-80 to 106-116 beats min-1 (P less than 0.05) after the sauna. The increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 7 publications
(9 reference statements)
5
60
0
Order By: Relevance
“…A statistically significant difference (p = 0.0105) in BML [%] was observed between the sexes (0.60% and 0.63%, respectively). The average BML [kg] in our research was similar to that reported in men in other studies [23,33,42], but lower than that noted by Pilch et al [32]. The fact that women lost less body mass [kg] could be attributed to the fact that females are generally characterized by lower levels of total body water (48 ± 6%) [44] and a higher content of adipose tissue, which reduces sweating, evaporation and BML [kg] [12,14].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A statistically significant difference (p = 0.0105) in BML [%] was observed between the sexes (0.60% and 0.63%, respectively). The average BML [kg] in our research was similar to that reported in men in other studies [23,33,42], but lower than that noted by Pilch et al [32]. The fact that women lost less body mass [kg] could be attributed to the fact that females are generally characterized by lower levels of total body water (48 ± 6%) [44] and a higher content of adipose tissue, which reduces sweating, evaporation and BML [kg] [12,14].…”
Section: Discussionsupporting
confidence: 80%
“…Temperatures between of 80 and 90°C at face level are considered optimal for most people [23]. The composition of the human body changes under such thermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained for evaluation of the effect of body overheating on TAG levels are inconsistent. Both, lack of the effect of sauna on TAG levels [32], and elevated TAG levels after a single sauna session in the male subjects [33] have been reported. The present study found a small and statistically insignificant increase in HDL cholesterol fraction level.…”
Section: Effect Of Sauna Bathing On Lipid Profile In Men O R I G I N mentioning
confidence: 99%
“…In sport, it is very often used as one of the training modalities [7][8][9][10][11][12]. It activates many body systems, including the endocrine system [4,[13][14][15][16][17]. The increase in the carbohydrates utilization, being a result of the increase in lactates concentration under thermal stress, was observed by many researchers [13,14,[18][19][20] and it can be explained by increased glycolysis.…”
Section: Introductionmentioning
confidence: 99%